Ethnobotanical study of medicinal plants used by the people of Mosop, Nandi County in Kenya - Z. C. Maiyo; S. N. Njeru; F. J. Toroitich; S. A. Indieka; M. A. Obonyo (Frontiers Media S.A., 2024)
Background: Throughout the history, nature has provided mankind with most of their basic needs, which include food, shelter, medicine, clothes, flavours, scents as well as raw materials. Given that they are an integral part of cultural heritage, medicinal plants have played a significant role in human healthcare systems around the world. Investigating various biological resources for use as medicines requires ethnomedicinal studies.Methods: Data on utilization of ethnomedicinal plants from local healers in Kenya's Mosop Sub-County in Nandi County was documented through open-ended, semi-structured questionnaires. A number of quantitative indices, such as the Use Citation (UC), Informant Consensus Factor (ICF), Use Value (UV), Frequency of Citation (FoC) and Relative Frequency of Citation (RFC) were used to convey the potential medical benefits, vitality and variety of the ethnomedicine.Results: 102 informants provided information on 253 ethnomedicinal plant species, classified into 74 families. There were 249 native plant species identified, along with few exotic species: Senegalia senegal (L.) Britton, Persea americana Mill, Carica papaya L. and Solanum betaceum Cav. Of all recorded species, 32% and 27% were herbs and trees, respectively. Among plant parts, leaves were most frequently utilized (27%) and roots (26%), while decoctions (21%) were the most widely used formulations. The dominant family was Asteraceae, with 28 species, followed by Lamiaceae, with 19 species. The highest ICF value was 0.778 for a number of parasitic and infectious illnesses, including ringworms, athlete's foot rot, tetanus, typhoid, intestinal parasites, abscesses, malaria, and amoebiasis. The study's data validates the region's widespread use of traditional medicinal plant remedies.Conclusion: The current study will lay a foundation of knowledge for future research investigations. The abundance of knowledge regarding ethnomedicinal species and their medicinal applications will stimulate further phytochemical and pharmacological research, which could lead to the discovery of potentially significant pharmaceuticals.